Do changes in climate patterns in wintering areas affect the timing of the spring arrival of trans‐Saharan migrant birds? - Oscar Gordo; Lluís Brotons; Xavier Ferrer; Pere Comas (Global Change Biology, 2005)
The life cycles of plants and animals are changing around the world in line with the predictions originated from hypotheses concerning the impact of global warming and climate change on biological systems. Commonly, the search for ecological mechanisms behind the observed changes in bird phenology has focused on the analysis of climatic patterns from the species breeding grounds. However, the ecology of bird migration suggests that the spring arrival of long‐distance migrants (such as trans‐Saharan birds) is more likely to be influenced by climate conditions in wintering areas given their direct impact on the onset of migration and its progression. We tested this hypothesis by analysing the first arrival dates (FADs) of six trans‐Saharan migrants (cuckoo Cuculus canorus , swift Apus apus , hoopoe Upupa epops , swallow Hirundo rustica , house martin Delichon urbica and nightingale Luscinia megarhynchos ), in a western Mediterranean area since from 1952 to 2003. By means of multiple regression analyses, FADs were analysed in relation to the monthly temperature and precipitation patterns of five African climatic regions south of the Sahara where species are thought to overwinter and from the European site from where FADs were collected. We obtained significant models for five species explaining 9–41% of the variation in FADs. The interpretation of the models suggests that: (1) The climate in wintering quarters, especially the precipitation, has a stronger influence on FADs than that in the species' potential European breeding grounds. (2) The accumulative effects of climate patterns prior to migration onset may be of considerable importance since those climate variables that served to summarize climate patterns 12 months prior to the onset of migration were selected by final models. (3) Temperature and precipitation in African regions are likely to affect departure decision in the species studied through their indirect effects on food availability and the build‐up of reserves for migration. Our results concerning the factors that affect the arrival times of trans‐Saharan migrants indicate that the effects of climate change are more complex than previously suggested, and that these effects might have an interacting impact on species ecology, for example by reversing ecological pressures during species' life cycles.

Changed plant and animal life cycles from 1952 to 2000 in the Mediterranean region - Josep Peñuelas; Iolanda Filella; PerE. Comas (Global Change Biology, 2002)
The available data on climate over the past century indicate that the earth is warming. Important biological effects, including changes of plant and animal life cycle events, have already been reported. However, evidence of such effects is still scarce and has been mostly limited to northern latitudes. Here we provide the first long‐term (1952–2000) evidence of altered life cycles for some of the most abundant Mediterranean plants and birds, and one butterfly species. Average annual temperatures in the study area (Cardedeu, NE Spain) have increased by 1.4 °C over the observation period while precipitation remained unchanged. A conservative linear treatment of the data shows that leaves unfold on average 16 days earlier, leaves fall on average 13 days later, and plants flower on average 6 days earlier than in 1952. Fruiting occurs on average 9 days earlier than in 1974. Butterflies appear 11 days earlier, but spring migratory birds arrive 15 days later than in 1952. The stronger changes both in temperature and in phenophases timing occurred in the last 25 years. There are no significant relationships among changes in phenophases and the average date for each phenophase and species. There are not either significant differences among species with different Raunkiaer life‐forms or different origin (native, exotic or agricultural). However, there is a wide range of phenological alterations among the different species, which may alter their competitive ability, and thus, their ecology and conservation, and the structure and functioning of ecosystems. Moreover, the lengthening of plant growing season in this and other northern hemisphere regions may contribute to a global increase in biospheric activity.